Bacterial Community Profiles in the Fluid of Four Pitcher Plant Species (Nepenthes spp.) Grown in a Nursery - ANDREE SIEGARA; . YOGIARA (Indonesian Society for microbiology, 2009)
Nepenthes is one of the Indonesian tropical carnivorous plants. The plant has a pitcher-like structure containing fluid for digesting insects. There are many microorganisms growing in the pitcher fluid. Different species of pitcher plants and planting sites could also contribute either to the diversity or the abundance of microorganism inhabiting the pitcher fluid. To assess the bacterial community variation in the fluid of pitcher plants grown in a nursery, amplified ribosomal DNA restriction analysis (ARDRA) was used. Four specimens of N. gracilis, N. truncata, N. veitchii and N. bicalcarata were obtained from Suska Nursery, Ciderum Village, Caringin, Bogor, Indonesia. A total of 191 positive clones were analyzed by using ARDRA. A sum of 124 phylotypes was obtained, comprising 17 in N. gracilis, 7 in N. truncata, 45 in N. veitchii and 55 in N. bicalcarata. It is interesting to note that each specimen harbored unique phylotypes, meaning that no phylotypes generated from one specimen were found in any of other specimens.